A comparative study of using a wooden storage box and storage platform for white yam tuber storage - Timothy AKPENPUUN (Acta Agriculturae Slovenica, 2018)
The study was undertaken to evaluate the performances of an experimental box and platform, as storage structures for white yam tubers (Dioscorea rotundata Poir.). The criteria used for evaluation were the degree of mass loss during storage, tuber sprouting and rotting during the 20 weeks storageperiod: March - June 2015. Measurements of temperatures and relative humidity of the storage environment were taken three times daily during the period. Mass loss in each tuber was measured weekly while sprouts were removed from tubers weekly. Results show that the average temperature and relative humidity in the experimental box were 29.7 °C and 78.6 % respectively, while for the platform, they were 30.7 °C and 76.5 %., respectively. Rotting was completely absent on tubers in both storage approaches. White yam tubers stored in the box exhibited a cumulative mass loss of 9 %, while on the platform, it was15.0 %. The experimental box performed better in respect to mass loss and nutritional composition.